Hypoxia stimulates the proliferation of rat neural stem cells by regulating the expression of metabotropic glutamate receptors: an in vitro study - Chen, X; Liu, Y; Zhang, Z; Miao, X; Tian, Y; Yao, L; Liu, J; Lu, H; Liu, Y (Cellular and Molecular Biology, 2016)
Neural stem cells (NSCs) reside in not only developing, but also adult brain with specialized microenvironments that regulate their function. In vitro and in vivo studies have revealed strong regulatory links between hypoxic/ischemic insults and activation of NSCs. However, the underlying mechanisms remain unclear. Here, we show that proliferating NSCs isolated from rat E15.5 cortex expressed functional metabotropic glutamate receptor (mGluR) subtype 3-7. Hypoxic exposure regulated their expression in NSCs in mRNA and protein levels. Activation of mGluRs by glutamate or Trans-ACPD (a non subtype-selective mGluRs agonist) sensitized NSCs to the growth effects of hypoxia. Pharmacological blockade of ionotropic glutamate receptor (iGluR) using MK-801 did not attenuate the action of glutamate in NSCs. Furthemore, we used the group specific mGluR agonists DHPG, LY 379268 and L-AP4 to explore which mGluR subtypes are responsible for stimulating NSCs proliferation after hypoxia. The results suggested that hypoxia increased expression of group I mGluR5 and significantly enhanced the NSCs proliferation. We conclude that hypoxia regulates the expression of mGluRs in proliferating NSCs and the dynamic expression of mGluRs induced by hypoxia may be one of the mechanisms of hypoxia stimulated NSCs activation. Regulation of mGluRs in NSCs might be a useful tool in the experimental cell therapy of hypoxic/ischemic injuries of CNS.